Rifabutin versus rifampicin bactericidal and antibiofilm activities against clinical strains of Staphylococcus spp. isolated from bone and joint infections. (14th January 2022) - Thill, Pauline; Robineau, Olivier; Roosen, Gabrielle; Patoz, Pierre; Gachet, Benoit; Lafon-Desmurs, Barthélémy; Tetart, Macha; Nadji, Safia; Senneville, Eric; Blondiaux, Nicolas
Abstract: Background: Staphylococci account for approximately 60% of periprosthetic joint infections (PJIs). Rifampicin (RMP) combination therapy is generally considered to be the treatment of choice for staphylococcal PJIs but carries an important risk of adverse events and drug–drug interactions. Rifabutin (RFB) shares many of the properties of rifampicin but causes fewer adverse events. Objectives: To compare the minimal inhibitory concentration (MIC), the minimum bactericidal concentrations (MBC), and the minimum biofilm eradication concentrations (MBEC) of rifabutin and rifampicin for staphylococcal clinical strains isolated from PJIs. Methods: 132 clinical strains of rifampicin-susceptible staphylococci [51 Staphylococcus aureus (SA), 48 Staphylococcus epidermidis (SE) and 33 other coagulase-negative staphylococci (CoNS)] were studied. The MBC and the MBEC were determined using the MBEC® Assay for rifabutin and rifampicin and were compared. Results: When compared with the rifampicin MIC median value, the rifabutin MIC median value was significantly higher for SA ( P < 0.05), but there was no statistically significant difference for SE ( P = 0.25) and CoNS ( P = 0.29). The rifabutin MBC median value was significantly higher than that of rifampicin for SA ( P = 0.003) and was lower for SE ( P = 0.003) and CoNS ( P = 0.03). Rifabutin MBEC median value was statistically lower than that of rifampicin for all strains tested. Conclusions: Using the determination of MBEC values, our study suggests that rifabutin is more effective than rifampicin against clinical strains of Staphylococcus spp. obtained from PJIs. Using MBECs instead of MICs seems to be of interest when considering biofilms. In vivo higher efficacy of rifabutin when compared with rifampicin needs to be confirmed.